(untitled) (Zoological Records and Reviews, 2024)
Community participation in wildlife conservation – encompassing citizen science monitoring, co-managed protected areas, community-based natural resource management, and stakeholder engagement in conservation planning – is increasingly recognised as essential for achieving durable biodiversity outcomes at landscape scales. This study evaluates the conservation effectiveness and social legitimacy of community participation approaches across 42 wildlife conservation initiatives in Denmark, the Netherlands, and Spain using a mixed-methods framework combining biodiversity outcome data (n = 14,284 species records), governance quality assessments (IUCN good governance criteria), and structured social surveys (n = 2,184 participants). Initiatives with high community participation scores (CPS >= 7/10) showed significantly better wildlife biodiversity outcomes than those with low participation (CPS < 4/10) across all three countries (mean inside-initiative species richness ratio 1.48 +- 0.18 vs. 1.12 +- 0.14 relative to outside; t(40) = 6.84, p < 0.001). Citizen science programmes contributed 38.4% of total species occurrence records in high-participation initiatives, with record quality comparable to professional surveys (Cohen’s kappa = 0.84 +- 0.06 for identification accuracy). Social surveys confirmed that perceived fairness of benefit-sharing was the strongest predictor of long-term participation willingness (beta = 0.58 +- 0.09, p < 0.001), exceeding direct economic incentives (beta = 0.34 +- 0.09) and ecological awareness (beta = 0.28). Initiatives combining citizen science, co-governance, and direct community benefit showed the highest combined biodiversity and social outcomes. These findings provide an evidence base for designing community participation frameworks under the Kunming-Montreal GBF Target 22 (inclusive conservation governance) and EU Nature Restoration Law community engagement obligations.